Literasi Media Digital Berbasis Praktik: Refleksi Pelatihan Penggunaan Media Sosial Sehat di SMK Manggala Tangerang - Adhvidya Adhvidya; Rifky Maulana (BADAN PENERBIT STIEPARI PRESS, 2025)
This community engagement program, conducted by lecturers from Universitas Pamulang, aimed to enhance digital media literacy among students at SMK Manggala Tangerang in response to the growing challenges of social media consumption and content creation in the digital age. Recognizing the high usage of social platforms among youth—often without adequate literacy or ethical awareness—the program employed a participatory, practice-based, and reflective approach. Training materials covered essential topics such as identifying hoaxes, protecting digital privacy, developing personal branding, and understanding online communication ethics. The methods applied included interactive lectures, group discussions, and hands-on exercises that encouraged active participation and critical reflection. The evaluation process involved observation, questionnaires, and interviews, which revealed significant improvements in students’ understanding of media literacy principles and a shift toward more critical and responsible digital behavior. Students reported increased confidence in filtering online information, managing their digital identities, and engaging more ethically on social media platforms. Furthermore, the program fostered a sense of awareness regarding the broader societal impact of digital communication, particularly in preventing misinformation and promoting constructive online interactions. Overall, the results demonstrate that practical, reflective training can effectively bridge the gap between theoretical knowledge and students’ lived digital experiences, fostering both ethical and critical digital character. These findings highlight the importance of integrating media literacy into school curricula as part of character education, especially to address the specific needs and challenges faced by Generation Z in navigating the complexities of the digital era.